Տեղահանված հայերի փոխադրումը Ամերիկա Երկրորդ աշխարհամարտից հետո - Տիգրան Ղանալանյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
После окончания Второй мировой войны оказавшиеся в Германии, Австрии, Италии несколко тысяч армян, главным образом из СССР, отказались репатриироваться, страшась ожидающих их репрессий в Советском Союзе. After the end of the World War II some thousands of Armenians, mainly from the USSR, who had appeared in Germany, Austria, Italy, refused to be repatriated - being afraid of the repressions expecting them in the Soviet Union.
Keywords: History; Armenian Diaspora